"Mal d'Afrique" in Italy: Translating African "Cultural Idioms of Distress" for more Effective Treatment. (9th October 2015) - Toffle, Mary Ellen
Abstract: The DSM-V (2013) states that culture assists in diagnosis because it shapes "the experience and expression of the symptoms, signs and behaviours that are criteria for diagnosis" (DSM-V, 2013, p. 14). The idea of "cultural idioms of distress" is presented as a description of suffering among people of the same cultural group. Various "cultural idioms of distress" have been identified worldwide, ranging from the 'Susto' (Central America) to 'Maladi Moun' (Haiti) which can be correlated with various psychopathologies (DSM-V, 2013). Recent statistics reveal that there are over 105, 000 Africans from the English-speaking countries of Nigeria, Ghana and Kenya currently living in Italy legally (Tuttitalia, 2014), and African immigration is increasing. The Executive Director of Frontex Fabrice Leggere stated that between 500, 000-1, 000, 000 immigrants could arrive in the near future, departing from Libya (ANSA, 2015 ). It is logical to assume that more people from English-speaking Africa will arrive, especially Nigerians. The immigrants who remain in Italy will have to learn Italian but they will use their own cultural concepts by translating them from English into Italian. Speaking with medical personnel and mental health professionals presents a huge challenge for both the patient and the care provider. This poses a problem of diagnosis for the healthcare professional, who must interpret both the words used and the underlying meanings of "cultural idioms of distress" which are an expression of the patient's culture. The purpose of this study is to identify basic definitions or names for illnesses and conditions of suffering given in English by English-speaking African immigrants. But what the words actually mean must be discovered and Italian healthcare professionals and social workers must understand the underlying meanings in order to provide effective diagnosis and care. Twelve African immigrants were interviewed from a selection of African countries where English is either the official language or one of the official languages. Discussions about how they arrived in Italy, their present condition and general illnesses were conducted in English. The interviews were recorded, transcribed and analysed. The immigrants demonstrated a few cultural idioms of distress describing both physical and mental illness and other difficulties. More research should be done on other African language groups. This information should then be communicated to all health and mental health professionals and incorporated into university professional training and continuing education programs in Italy.